2014
DOI: 10.1002/mrc.4178
|View full text |Cite
|
Sign up to set email alerts
|

DFT1H-1H coupling constants in the conformational analysis and stereoisomeric differentiation of 6-heptenyl-2H-pyran-2-ones: configurational reassignment of synargentolide A

Abstract: Density functional theory (DFT) (1) H-(1) H NMR coupling constant calculations, including solvation parameters with the polarizable continuum model B3LYP/DGDZVP basis set together with the experimental values measured by spectral simulation, were used to predict the configuration of hydroxylated 6-heptenyl-5,6-dihydro-2H-pyran-2-ones 1, 2, 4, and 7, allowing epimer differentiation. Modeling of these flexible compounds requires the inclusion of solvation models that account for stabilizing interactions derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…44 However, extraction of chemical shifts and J coupling constants by non-linear fitting of the spectra obtained from the natural product and the synthetic diastereoisomer highlighted slight differences disproving the revision. 45 Further predictive calculation of the coupling constants by DFT computation of four possible diastereoisomers suggested the configuration to be 13b . The simulation took advantage of the spin-spin option in the program Gaussian 09 46 which calculates the scalar coupling constant as a summation of Fermi contact, spin-dipolar, paramagnetic spin-orbit, and diamagnetic spin-orbit.…”
Section: Structural Revision Based On Computational Prediction Of Nmentioning
confidence: 99%
“…44 However, extraction of chemical shifts and J coupling constants by non-linear fitting of the spectra obtained from the natural product and the synthetic diastereoisomer highlighted slight differences disproving the revision. 45 Further predictive calculation of the coupling constants by DFT computation of four possible diastereoisomers suggested the configuration to be 13b . The simulation took advantage of the spin-spin option in the program Gaussian 09 46 which calculates the scalar coupling constant as a summation of Fermi contact, spin-dipolar, paramagnetic spin-orbit, and diamagnetic spin-orbit.…”
Section: Structural Revision Based On Computational Prediction Of Nmentioning
confidence: 99%
“…In particular, those containing the 5,6-dihydro-2 H -pyran-2-one unit with an R -configuration at the C-6 stereogenic center of the α,β-unsaturated δ-lactone exhibit antimicrobial, antifungal, and cytotoxic properties . It is believed that this well-known Michael acceptor constitutes the pharmacophoric moiety responsible for the biological properties of these 5,6-dihydro-2 H -pyran-2-ones from the mint family, , which resemble the antiproliferative activity against various cancer cell lines of (−)-pironetin, a potent inhibitor of tubulin assembly …”
mentioning
confidence: 99%
“…Molecules 2020, 25,1905 16 of 35 deprotection and acetylation of this compound (99) yields 96a and 96b, which were then converted to 88a and 88b, respectively (following the method shown earlier in Scheme 19). It is interesting to mention here that the calculation of density functional theory (DFT) NMR parameters has recently suggested that both the structures 88a and 88b are incorrect and 88c is the correct structure of the natural synargentolide A [60].…”
Section: Synargentolide Bmentioning
confidence: 99%
“…Compound 100b was synthesized [61] It is interesting to mention here that the calculation of density functional theory (DFT) NMR parameters has recently suggested that both the structures 88a and 88b are incorrect and 88c is the correct structure of the natural synargentolide A [60].…”
Section: Synargentolide Bmentioning
confidence: 99%